Prediksi Kebutuhan Alat Tulis Kantor Dengan Metode Fuzzy Logic Tsukamoto Di BPR Dana Mulia Sejahtera - Hendi Setiawan (Jurnal Bangkit Indonesia, 2020)
Processing inventory data manually by counting one by one and it is difficult to distinguish the types of inventory is very ineffective and inefficient, for that we need an application that can simplify performance and solve problems related to inventory processing. So we need a method to overcome various things, the method used is the Fuzzy Logic Tsukamoto method. Fuzzy Logic Tsukamoto is a technique or method used to overcome uncertainty in problems that have many answers. Based on existing problems, the authors analyze and design a new system that anticipates weaknesses in the running system without causing new problems. With Fuzzy logic Tsukamoto reasoning provides a way to understand system performance by assessing system input and output from observations.